HEPATITIS C VIRUS INFECTJON IN RENAL TRANSPLANTATION - Oya ÖVÜNÇ; Fundu TÜRKMEN; İzzet TİTİZ; A. Remzi DALAY; Kemal Nuri ÖZERKAN; Cihan ERSAN; Güler YAYLI (Turkish Journal of Gastroenterology, 2020)
-